Dix Ans d'Art Vivant 1945-1955. - Wehrlin, François (Saint-Paul-de-Vence : Fondation Maeght, 1966)
Albers, Josef ; Arp, Hans (Jean) ; Atlan, Jean-Michel ; Bacon, Francis ; Baumeister, Willi ; Bazaine, Jean ; Bissière, Roger ; Bonnard, Pierre ; Braque, Georges ; Burri, Alberto ; Calder, Alexander ; Chagall, Marc ; Delaunay, Sonia ; Dewasne, Jean ; Dubuffet, Jean ; Ernst, Max ; Estève, Maurice ; Fautrier, Jean ; Fontana, Lucio ; Francis, Sam ; Giacometti, Alberto ; Gorky, Arshile ; Gruber, Francis ; Hajdu, Etienne ; Hartung, Hans ; Hélion, Jean ; Herbin, Auguste ; Hofmann, Hans ; Kline, Franz ; de Kooning, Willem ; Lapicque, Charles ; Laurens, Henri ; Leger, Fernand ; Magnelli, Alberto ; Manessier, Alfred ; Martin, Etienne ; Masson, Andre ; Matisse, Henri ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Michaux, Henri ; Miro, Joan ; Moore, Henry ; Mortensen, Richard ; Nicholson, Ben ; Pasmore, Victor ; Picasso, Pablo ; Poliakoff, Serge ; Pollock, Jackson ; Reichel, Hans ; Richier, Germaine ; Riopelle, Jean-Paul ; Rouault, Georges ; Soulages, Pierre ; de Staël, Nicolas ; Sutherland, Graham ; Szenes, Arpad ; Tal-Coat, Pierre ; Tanguy, Yves ; Tobey, Mark ; Ubac, Raoul ; Vasarely, Victor ; van Velde, Bram ; Van Velde, Geer ; Vieira da Silva, Maria Elena ; Villon, Jacques ; Wols ; Yoshihara, Jiro
biog.
Frans
Dix Ans d'Art Vivant 1945-1955, Fondation Maeght, Saint-Paul-de-Vence, du 9 avril au 31 mai 1966
boek